Structural characterization and immunomodulatory activity of a novel polysaccharide from Panax notoginseng - Jiang, Xue-Lian; Ma, Gai-Fan; Zhao, Bin-Bin; Meng, Yan; Chen, Lin-Lin (Frontiers in Pharmacology, 2023)
A water-soluble polysaccharide (PNPB1) was isolated from rhizome of Panax notoginseng by anion exchange and gel permeation chromatography. The molecular weight of PNPB1 was determined to be 9.3×105 Da. Monosaccharide composition analysis indicated that PNPB1 consisted of Glc (88.2%), Gal (9.0%), Ara (2.4%) and trace GlcA, with the major backbone of (1→4)-linked α-Glcp, (1→6)-linked β-Glcp, and (1, 4→6)-linked β-Glcp. The immunoregulatory function of PNPB1 was further investigated in cyclophosphamide induced immunosuppressive mice and immune cells. The polysaccharide was found to significantly enhance murine body weight, improve their thymus and spleen indices and increase the white blood cells (WBC). PNPB1 significantly enhanced splenic lymphocyte proliferation, NO and cytokine (TNF-α, IL-2, IL-10 and IFN-γ) production, as well as the phagocytosis and TLR2 expression of peritoneal macrophages, indicating potent immunoenhancement effect. These findings provide a theoretical basis for elucidating the structure and immune activity of notoginseng polysaccharides.